Analytical solutions for heat transfer efficiency in metallic honeycombs using two-equation method. (July 2016) - Liu, H.; Yu, Q.N.; Zhang, Z.C.; Qu, Z.G.; Wang, C.Z.
Abstract: An analytical model based on corrugated wall using two-equation method is proposed to evaluate the heat transfer performance in the sandwiched metallic honeycomb heat exchanger under forced convection conditions. The local thermal non-equilibrium between cooling fluid and solid honeycombs is taken into account compared with corrugated wall model, effective medium model, and transfer matrix model. A general analytical solution carried out using introduced effective specific surface area to overcome the fin efficiency underestimation and corrugated wall overestimation shows extensive applicability in predicting the thermal performance index, which can be restated to represent corrugated wall model, transfer matrix model, and the effective medium model, respectively.